1994
DOI: 10.1128/aac.38.10.2317
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of 123 strains of Xanthomonas maltophilia to eight beta-lactams (including beta-lactam-beta-lactamase inhibitor combinations) and ciprofloxacin tested by five methods

Abstract: This study evaluated the susceptibility of 123 Xanthomonas maltophilia strains to ticarcillin, ticarcillinclavulanate, ampicillin, amoxicillin-clavulanate, ampicillin-sulbactam, piperacillin, piperacillin-tazobactam, imipenem, and ciprofloxacin by Kirby-Bauer disk, E test, and Sensititre dehydrated microdilution MIC and conventional agar dilution MIC methodology. Intermediate susceptibility breakpoints for members of the family Enterobacteriaceae were used. When results were analyzed as MICs for 50 and 90%Yo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 18 publications
7
41
0
Order By: Relevance
“…However, as results of this study also revealed, there are discrepant susceptibility data, particularly with disc diffusion for colistin, ticarcillin/clavulanate, and ciprofloxacin and with the E-test for ticarcillin/clavulanate, ciprofloxacin and, to a lesser extent, ceftazidime. There have been several reports related to the discordance between different susceptibility testing methods for S. maltophilia [6][7][8][23][24][25]. It has been previously reported by the NCCLS that for an acceptable performance of susceptibility tests, the overall categorical error rate should be \10%, of these B1.5% being VMEs and B3% being MEs [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, as results of this study also revealed, there are discrepant susceptibility data, particularly with disc diffusion for colistin, ticarcillin/clavulanate, and ciprofloxacin and with the E-test for ticarcillin/clavulanate, ciprofloxacin and, to a lesser extent, ceftazidime. There have been several reports related to the discordance between different susceptibility testing methods for S. maltophilia [6][7][8][23][24][25]. It has been previously reported by the NCCLS that for an acceptable performance of susceptibility tests, the overall categorical error rate should be \10%, of these B1.5% being VMEs and B3% being MEs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Pankuch et al [14] also found a poor correlation among five susceptibility testing methods evaluated against eight β-lactams (including β-lactam-β-lactamase inhibitor combinations) and ciprofloxacin antimicrobial agents against S. maltophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Agar dilution and microtiter broth dilution tests yielded MICs that correlated rather well (table 2). Previously, Pankuch et al [21] found time-kill curve assays to correlate best with MICs obtained with the agar dilution technique. Determination of FICs (table 3) with the aid of microtiter checkerboard titrations in broth and utilizing various antibiotic combinations revealed the combinations of rifampin + polymyxin B, ceftazidime plus ofloxacin, and cotrimoxazole plus timentin to exert additive/synergistic effects against the four test strains of S. maltophilia: these findings were expected as based on data presented by previous investigators [12][13][14][15]27].…”
Section: Discussionmentioning
confidence: 99%